2020
DOI: 10.1007/s00787-020-01509-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential utility of teacher and parent–teacher combined information in the assessment of Attention Deficit/Hyperactivity Disorder symptoms

Abstract: Background Consistent research findings indicate that parents and teachers observe genuinely different Attention Deficit/Hyperactivity Disorder (ADHD) behaviours in their respective settings. Objective To evaluate the utility of information provided by teacher informant assessments (INFAs) of ADHD symptoms, and the implications of aggregation algorithms in combing parents’ information, i.e. using ‘or-rule’ (endorsement by either one informant) vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Parents and teachers genuinely observe different ADHD behaviors with unique aspects of expression in their respective setting. Even with a low level of parentteacher agreement, information from both is important in detecting symptoms, defining trait levels and severity of impairment, and defining the diagnosis (Garcia-Rosales et al, 2021;McGrath, 2020). In particular, parents endorse more accurate information concerning low to moderate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Parents and teachers genuinely observe different ADHD behaviors with unique aspects of expression in their respective setting. Even with a low level of parentteacher agreement, information from both is important in detecting symptoms, defining trait levels and severity of impairment, and defining the diagnosis (Garcia-Rosales et al, 2021;McGrath, 2020). In particular, parents endorse more accurate information concerning low to moderate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Children’s families and schools are generally the first to distinguish the symptoms of ADHD, which is why most of the instruments used for a diagnosis involve an initial assessment of the child’s behavior by their teachers and parents ( Garcia-Rosales et al, 2020 ). Also, it is likely that the high expectations of school performance, which parents and teachers place on children, increase the need to find clinical explanations for school failure ( Santana-Vidal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (from Egypt and worldwide) have shown that parents report ADHD symptoms more frequently than teachers [19,20,[23][24][25][26][27][28][29] and that parents may not have age-appropriate behavioral expectations for their children causing overdiagnosis of ADHD. Parents were found to be more reliable in ratings of forgetfulness, whereas teachers were found to be more reliable reporters of deficits in sustained attention (teachers can quickly compare students and detect those poorly performing in a class task) [23,30]. In addition, mothers (the main informants in our study) were found to consistently report more inattention and hyperactivity symptoms than fathers (mothers spend longer times with children than fathers and many children behave better in the presence of their father) [23,24,28,31].…”
Section: Discussionmentioning
confidence: 99%